1979
DOI: 10.1111/j.2044-8317.1979.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the triangular method and the relationship of its unidimensional probabilistic models to three‐alternative forced‐choice signal detection theory models

Abstract: The experimental procedure involved in the application of the statistical triangle test and some of the limitations of this mothod are briefly discusscd. Two types of unidimensional distance models, the trianglo constant method and the normal Thurstone-Ura model, are briefly reviewed and the logistic Thurstone-Ura model is developod. The two versions of the Thurstone-Ura model are shown to be remarkably difforent from the corresponding versions of the three-altornative forced-choico signal detection thoory mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…It can be shown that Equation 30 is identical to the one obtained by Bradley (1963) and Frijters (1979b).…”
Section: Highly Correlated Observations; £2 =0supporting
confidence: 62%
See 1 more Smart Citation
“…It can be shown that Equation 30 is identical to the one obtained by Bradley (1963) and Frijters (1979b).…”
Section: Highly Correlated Observations; £2 =0supporting
confidence: 62%
“…Thus, it is argued that a good decision procedure is to select the vertex most distant from the other two. Bradley (1963) and Frijters (1979b) have presented an analysis of this task based on that decision rule. Frijters, Kooistra, and Vereijken (1980) have published tables on d' as a function of the percentage of correct responses for the three-alternative oddity task.…”
Section: Three-interval Oddity Paradigmmentioning
confidence: 99%
“…The present experiment deals with these four models, and since they were extensively described in Frijters (1979), only a brief summary of their theory is given here, after which the aims of the experiment are described.…”
mentioning
confidence: 99%
“…In a recent paper (Frijters, 1979), one of these triangular method models was called the Thurstone-Ura model, and it was compared theoretically to a similar distance model for the 3-AFC procedure, called the normal 3-AFC SOT model. In the same paper, the logistic variants of these models were developed and compared with each other.…”
mentioning
confidence: 99%
See 1 more Smart Citation